Application of Arbuscular Mycorrhiza and Organic Fertilizer on the Growth and Yield of Marigold (Tagetes Erecta L.) - Made Satya Adhi Nugraha; Yohanes Parlindungan Situmeang; Desak Ketut Tristiana Sukmadewi (Program Studi Magister Sains Pertanian Program Pascasarjana Universitas Warmadewa, 2025)
This study aims to determine the effect of the application of arbuscular mycorrhizal fungi and solid organic fertilizer doses on the growth and yield of marigold plants (Tagetes erecta L.). This research was conducted at the experimental field of the Agrotechnology Study Program, Faculty of Agriculture, Warmadewa University. Study used a Randomized Block Design (RBD) consisting of two factors arranged factorially. The first factor was the arbuscular mycorrhizal fungi dose, consisting of three levels: M1 = 10 g/plant, M2 = 15 g/plant, M3 = 20 g/plant. The second factor was the solid organic fertilizer dose, also consisting of three levels: O1 = 10 tons/ha, O2 = 20 tons/ha, O3 = 30 tons/ha. The results showed that the interaction between arbuscular mycorrhizal fungi and solid organic fertilizer had a significant effect on plant height, number of flowers, and flowering time. The highest number of flowers was obtained in the treatment of 20 g arbuscular mycorrhizal fungi and 30 tons/ha solid organic fertilizer (M3O3), with an average of 10.83 florets, while the fastest flowering time was recorded at 46.83 days. Meanwhile, the arbuscular mycorrhizal fungi factor alone significantly affected the number of leaves, number of branches, flower diameter, root length, and root weight. The solid organic fertilizer factor significantly affected the number of leaves, flowering time, and root weight. The combination of 20 g arbuscular mycorrhizal fungi and 30 tons/ha solid organic fertilizer proved most effective in supporting growth and flower development in marigold cultivation